ANALISIS ERGONOMI MENGGUNAKAN METODE REBA TERHADAP POSTUR PEKERJAAN PADA BAGIAN PEMINDAHAN GALON AIR PADA PT. XYZ - Muhammad Refaldi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research aims to analyze work posture in water gallon transfer activities using the Rapid Entire Body Assessment (REBA) method at PT. XYZ. The REBA method is used to assess the risk of musculoskeletal injury based on body posture, force applied, and activities performed. Direct observation and video recording were used to collect work posture data. The results of the REBA analysis show that work postures in water gallon transfer activities have a high risk of injury. Proposed improvement recommendations include the use of assistive devices, changes to work station design, and training in proper lifting techniques to reduce the risk of injury to workers. Implementation of appropriate ergonomic solutions is expected to improve work health and safety as well as the efficiency of the water gallon transfer process.